Differential gene expression profiles of human monocyte-derived antigen presenting cells in response to Penicillium marneffei: Roles of DC-SIGN (CD209) in fungal cell uptake - Piyaporn Ngaosuwankul (2018)
DNA microarray technology was used to determine the gene expression profile of human monocyte-derived macrophages (hMDMs) after stimulation by Penicillium marneffei yeast. The expression levels of 175 macrophage genes were found to be altered by a minimum of two-fold in magnitude following 4 hours of P. marneffei exposure. Among those, 41 genes were upregulated in activated hMDMs while 134 genes were downregulated. Real-time PCR and RT-PCR were performed to further examine gene expression associated with the inflammatory response. Increased levels of TNF-α and IL-1β gene expression in both hMDMs and human monocyte-derived dendritic cells (hMoDCs) were observed after stimulation by P. marneffei yeast. Furthermore, the genes encoding T-bet, IL-6 and ICAM-1 were also upregulated in hMDMs. Functional analysis of the adhesion of P. marneffei to dendritic cell-specific intercellular adhesion molecule-3 grabbing non-integrin (DC-SIGN, CD209) was performed in hMoDCs since the microarray data revealed an increased expression of DC-SIGN in activated hMDMs. We found that DC-SIGN-Fc bound preferentially to P. marneffei yeast rather than to conidia. Moreover, an anti-DC-SIGN monoclonal antibody inhibited the binding of P. marneffei yeast to hMoDCs, but did not inhibit endocytosis of P. marneffei yeast. The mannose receptor, on the other hand, was important in both adhesion and phagocytosis. These results suggest that P. marneffei may exploit DC-SIGN as a receptor to facilitate the systemic spread of infection. Taken together, our study demonstrates the usefulness of microarray technology in generating valuable expression data to permit conventional immunologic investigations of host-fungal interactions.